"An alternative discourse": Local interpreters of antiquities in the Ottoman Empire. (August 2015) - Anderson, Benjamin
<x content-type="archive" xml:space="preserve">Abstract</x> The premise of Ottoman indifference to "antiquities" was already widely assumed by early modern travelers and archaeologists and continues to inform contemporary discussion of cultural patrimony in post-Ottoman nations. However, it is contradicted by numerous accounts of local interpretations of ancient monuments and local resistance to the efforts of outsiders to remove antiquities. Local interpretations of monuments constituted an alternative discourse that cohered around a set of recurring concerns, while also developing over time. The potential of these local interpretations to expand the discourse of academic archaeology has been obscured by their classification as elements of a timeless folklore, which is understood to speak to the customs and manners of the interpreters, not to the objects of interpretation.